(untitled) (Experimental biology, 2015)
The biosensor was isolated for ecological monitoring and clinical diagnostic from ripening ears of wheat. The sensitive biosensor was isolated by chromatography on nanostructures carbon sorbent ‘Nanocarbosorb’ produced by Scientific Technical Industry Center “Zhalyn” (Almaty city). Conditions of isolation of the biosensor were optimized. The investigation of activity of the biosensor shown that this enzyme has high affinity to ammonium ions that aloud to determine the concentration of ammonium in range from 0,2 μM to 10μM therefore our biosensor can be applicable for earlier detection of anthropogenic pollution from the water reservoirs. High sensitivity of biosensor for determination of concentration of NADPH and 2-oxoglutarate make its very convenient for application in clinical diagnostic.